Minimnya Refleksi Diri Siswa dalam Evaluasi Pembelajaran Matematika: Tantangan dan Solusi Berbasis Teori dan Praktik - Fadhilah Nur Sa'diyyah; Ibnu Hajar; Fitri Fitri (Journal of Mathematics, Statistics and Applications, 2025)
The lack of student self-reflection in evaluating mathematics learning is a serious challenge that hinders the development of conceptual understanding and critical thinking skills. This literature review aims to identify factors that can lead to a lack of reflective practice in mathematicsclasses, highlight the role of teachers as facilitators, and recommend effective strategies based on educational theory and field practice. The results of this study indicate that self-reflection is still rarely actively facilitated, both by teachers and evaluation systems that emphasize the end productrather than the process. Teachers have a strategic role in guiding students through directed reflection, while metacognitive approaches and collaborative learning can encourage the growth of reflective habits. Transformation of the evaluation system that values the thinking process is needed so that students develop into independent, conscious, and critical learners. Thus, building a reflective culture is not only about improving learning outcomes, but also shaping character and lifelong learning competencies.